STRUKTURASI DALAM INDUSTRI MEDIA BARU DI INDONESIA - Syarofa, Sherina (Universitas 17 Agustus 1945 Surabaya, 2024)
The presence of Wattpad in Indonesia has created new media dynamics that are interesting to study using political economic theory by Vincent Mosco. This theory is related to the current globalization of political and economic media and explains the transition from old media to new media. Mosco's theory shows how the structure of the media industry is shaped by economic (such as content monetization and corporate profits) and political (such as government regulation and control) interests. On Wattpad, this shows how companies monetize user content and how government laws can impact access and freedom of expression online. The method used in this study is a case study and a qualitative approach based on critical traditions and paradigms. This study uses secondary data originating from documentation, and primary data comes from observation and interviews. The theory used in this study is Vincent Mosko's Political Economy of Communication Theory. This study shows that overall, the structuration of Wattpad in Indonesia, through the lens of Vincent Mosco's theory, shows that this new media platform not only provides space for creativity and expression but also shapes the structure of the media industry, which changes the dynamics of power, resource distribution, and interaction. social. Thus, it illustrates how new media contributes to significant changes in the communications and publishing landscape in Indonesia more broadly. By using Vincent Mosko's theory to build the structure of Wattpad in Indonesia, several important implications can be seen. One is that Wattpad allows for more diverse content and includes stories that highlight local culture and experiences that may be underrepresented in first-stream media. An example of a Wattpad story that raises a cultural theme is